Environmental Performance Reviews: Montenegro - United Nations (United Nations, 2015)
The United Nations Economic Commission for Europe (ECE) Environmental Performance Review Programme assesses progress made by individual countries in reconciling their economic and social development with environmental protection, as well as in meeting international commitments on environment and sustainable development. The Environmental Performance Review Programme assists countries to improve their environmental policies by making concrete recommendations for better policy design and implementation. Environmental Performance Reviews help to integrate environmental policies into sector-specific policies such as those in agriculture, energy, transport and health. Through the peer review process, the reviews promote dialogue among Governments about the effectiveness of environmental policies as well as the exchange of practical experience in implementing sustainable development and green economy initiatives. They also promote greater Government accountability to the public. The present publication contains the third Environmental Performance Review of Montenegro. The review takes stock of the progress made by Montenegro in the management of its environment since the country was reviewed in 2007 for the second time. It assesses the implementation of the recommendations contained in the second review. The third review covers policymaking, implementation and the financing of environmental policies and projects. It discusses waste management and the protection of water resources, as well as impacts of and measures to address climate change. The review makes suggestions for strengthening efforts towards a comprehensive and systemic response to sustainable development challenges. The publication is aimed at officials and experts working for public authorities responsible for environmental policy, representatives of civil society, the business community, academia and the media.